Peran Penting Pemilik Kucing Terhadap Kesehatan Kucing Peliharaan Di Wilayah Tambaksari, Surabaya - Arimurti, Anindita Riesti Retno; Rohmayani, Vella; Artanti, Dita; Daesusi, Ruspeni; Muhammad Alvian; Veronita Leni Anggraeni (Yayasan Rahmatan Fidunya Wal Akhirah, 2023)
Cats are one of the animals that are often kept as pets by humans. However, it turns out that cats can act as hosts for transmitting various types of dangerous diseases, both caused by endoparasites and ectoparasites. Therefore, the role of cat owners is very important in maintaining the health of their pet cats. Remembering that a cat's life depends on the care it provides. This service activity aims to educate cat owners about the dangers, symptoms and ways to prevent endoparasite and ectoparasite infections in their pet cats. Maintaining the health of your pet cat is important, because the cat's health can affect the health of its owner. This is because some diseases in cats can be transmitted to humans. The method used in this service is a presentation and discussion with the cat owner, after which it continues with the activity of examining the cat's hair and distributing shampoo and cat food. To measure the level of understanding of pet cat owners, a pretest (before the activity) and posttest (at the end of the activity) were carried out. This activity was carried out in RW 001, RT 07, RT 08, and RT 11 Tambaksari, Surabaya, and was attended by 32 pet cat owners, namely 14 domestic cats, 8 Angoras, 6 Persians, and 3 Himalayans. The average pre-test score was 54.07 points, while the average post-test score was 73.70 points. This means that there is an increase in pet cat owners' understanding regarding the symptoms, dangers and ways to prevent endoparasite and ectoparasite infections in cats. It is hoped that this educational activity will be sustainable so that cat owners can always look after and pay attention to the health of their pet cats. Keywords : cats, ectoparasite, endoparasite, Tambaksari